2013
DOI: 10.1002/pri.1551
|View full text |Cite
|
Sign up to set email alerts
|

Why Do We Do As We Do? Factors Influencing Clinical Reasoning and Decision‐Making among Physiotherapists in an Acute Setting

Abstract: Clinical reasoning is a complex and constantly evolving process. Contextual factors such as economy and politics are not easily changed, but factors such as the patient and the physiotherapist as a person are more tangible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
43
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(61 citation statements)
references
References 24 publications
(31 reference statements)
5
43
0
1
Order By: Relevance
“…Findings from qualitative studies suggest that clinical reasoning is influenced by the context, characterized by flexible decisions and actions, conducted in collaboration with the client and guided by the physiotherapists' cognitive and reflective processes (Cruz, Moore, and Cross, 2012;Doody and McAteer, 2002;Edwards et al, 2004;Holdar, Wallin, and Heiwe, 2013;Josephson, Bülow, and Hedberg, 2011;Masley et al, 2011;Smart and Doody, 2007;Smith, Higgs, and Ellis, 2008;Wainwright, Shepard, Harman, and Stephens, 2011). However, we found no studies that showed physiotherapists focus on client behaviour change in their clinical reasoning.…”
Section: Introductionmentioning
confidence: 65%
See 2 more Smart Citations
“…Findings from qualitative studies suggest that clinical reasoning is influenced by the context, characterized by flexible decisions and actions, conducted in collaboration with the client and guided by the physiotherapists' cognitive and reflective processes (Cruz, Moore, and Cross, 2012;Doody and McAteer, 2002;Edwards et al, 2004;Holdar, Wallin, and Heiwe, 2013;Josephson, Bülow, and Hedberg, 2011;Masley et al, 2011;Smart and Doody, 2007;Smith, Higgs, and Ellis, 2008;Wainwright, Shepard, Harman, and Stephens, 2011). However, we found no studies that showed physiotherapists focus on client behaviour change in their clinical reasoning.…”
Section: Introductionmentioning
confidence: 65%
“…Metacognition is used to monitor and control the process, thereby enhancing the quality of clinical decisions and actions (Marcum, 2012). The physiotherapist's experience, education (Holdar, Wallin, and Heiwe, 2013;Wainwright, Shepard, Harman, and Stephens, 2011) and approach to the reasoning process (Edwards et al, 2004;Holdar, Wallin, and Heiwe, 2013;Smith, Higgs, and Ellis, 2008) are also important. In addition to the prerequisites of the physiotherapist, the clinical setting (Holdar, Wallin, and Heiwe, 2013;Masley et al, 2011) and the client's status (Josephson, Bülow, and Hedberg, 2011) contribute to the characteristics of the reasoning process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Limitations in service delivery combined with increased responsibility can lead to dilemmas, as the appropriate course of action cannot be achieved because of external barriers (34); this can create tension between political governance and the professional accountability of street-level bureaucrats (35). Recent studies show that influence of contextual factors and external circumstances such as economy, duration of stay, organization and culture affect physiotherapists' and other professionals' clinical reasoning and decision-making (36)(37)(38)(39)(40)(41). The results from our study reveal that these factors also affect the quality of rehabilitative work and the process of patient transition from SpHC to further PrHC follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical reasoning demands a thorough understanding of the appropriate clinical subject matter; 5,6 sources such as textbooks and online resources provide access to information that can support and facilitate the clinical decision-making process. Studies in the 1990s examining physiotherapists' use of clinical resources indicated that clinicians primarily used textbooks and spoke with other clinicians to find clinical information.…”
mentioning
confidence: 99%